The impact of changes in agro-climatic resources on pea yield in the new climatic period of 1991–2020 in the Kirov region - Irina V. Lyskova; Olga E. Sukhoveeva; Svetlana S. Pislegina (Аграрная наука Евро-Северо-Востока, 2025)
The study is devoted to assessing the current state of agro-climatic resources and their impact on pea yield in Falenki district of the Kirov region. We used data from the Falenki Meteorological Station for 1991–2020. (in comparison with the base period of 1961–1990) and the results of the competitive variety testing of 7 cultivars of peas at the Falenki Breeding Station, a branch of the for 2011–2020. In the period of 1991–2020, a steady increase in air temperature was detected at a rate of 0.44 °C/10 years, while moisture availability remained at the same level. The pea cultivars ‘Krasnoufimsky 93’, ‘Ryabchik’, ‘Severyanin’, ‘Falensky usatii’, ‘Vita’, ‘Falensky Yubileyny’, ‘Vyatich’, which were the objects of the study, were distinguished by a wide yield dispersion and high coefficients of its variation (36.3–55.0 %). As a result of clustering, the cultivars were divided into three groups according to the yield, one of which was a single feed cultivar ‘Vyatich’, the other was a pair of valuable and related cultivars ‘Falensky Usatii’ and ‘Falensky Jubilee’, the third united all other cultivars. Correlation analysis indicated an average negative relationship between yield and air temperature in summer (-0.402...-0.560) and a positive effect of precipitation and increased humidification (0.455...0.669). Significant regression dependences of crop yields on air temperature in July were obtained, which determined 39.4–54.0 % of the productivity variance. According to the results of a two-factor analysis of variance, both weather conditions (76.1 %) and varietal characteristics (6.3 %) had a significant impact on pea yields.